The Effect Of Current Ratio, Debt To Asset Ratio, Net Profit Margin, And Exchange Rate On The Stock Prices Of Oil Companies: Case Study on Petroleum Companies Listed on the Indonesia Stock Exchange for the Period 2019-2024 - Yoyon Supriadi; Ludianthara Hendrawan; Aang Munawar; Ratih Puspitasari; Zul Azhar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine whether there is Influence of Current Ratio, Debt to Asset Ratio, Net Profit Margin, and Exchange Rate on the Stock Prices of Sub-Sector Crude Oil Companies Listed on the Indonesia Stock Exchange for the Period of 2019-2024. The sample in this study consists of 13 companies selected based on purposive sampling technique. Using purposive sampling, 10 companies were obtained as samples over a period of 6 years, resulting in a total of 60 data points. The analytical method used in this study is descriptive statistics, using multiple linear regression analysis with the help of SPSS 23 software. The results of this study indicate that the Current Ratio variable affects Stock Prices, Debt to Asset Ratio affects Stock Prices, Net Profit Margin partially does not affect Stock Prices, and Exchange Rate does not affect Stock Prices. Meanwhile, Current Ratio, Debt to Asset Ratio, Net Profit Margin and Exchange Rate simultaneously have a significant effect on Stock Prices. Keywords : Current Ratio, Debt to Asset Ratio, Net Profit Margin, Exchange Rate, Stock Prices